2022
DOI: 10.3390/insects13080701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Receptor on Juvenile Hormone Signal and Fecundity in Spodoptera litura (F.)

Abstract: Insulin signaling can regulate various physiological functions, such as energy metabolism and reproduction and so on, in many insects, including mosquito and locust. However, the molecular mechanism of this physiological process remains elusive. The tobacco cutworm, Spodoptera litura, is one of the most important pests of agricultural crops around the world. In this study, phosphoinositide 3-kinase (SlPI3K), protein kinase B (SlAKT), target of rapamycin (SlTOR), ribosomal protein S6 kinase (SlS6K) and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…27 RNAi knockdown of IR delayed ovarian development and resulted in a lower JH titer. 53 Similarly, mutation of IR reduced JH synthesis in D. melanogaster. 54 These findings suggested that the insulin pathway is involved in the insect diapause process by altering the JH synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 RNAi knockdown of IR delayed ovarian development and resulted in a lower JH titer. 53 Similarly, mutation of IR reduced JH synthesis in D. melanogaster. 54 These findings suggested that the insulin pathway is involved in the insect diapause process by altering the JH synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the JH analog methoprene rescued ovarian development in dsInR ‐injected Culex pipiens 27 . RNAi knockdown of IR delayed ovarian development and resulted in a lower JH titer 53 . Similarly, mutation of IR reduced JH synthesis in D. melanogaster 54 .…”
Section: Discussionmentioning
confidence: 99%
“…With PI3K/Akt, IRS binds to PI3K, activating Akt, which phosphorylates and inhibits a class O of forkhead box transcription factor (FOXO) and its downstream targets ( 27 , 28 ), including developmental growth and differentiation regulators in conserved pathways such as hedgehog signaling ( 29 31 , see 32 for an example of FOXO activity in adults). Akt can also activate the cAMP-response element binding protein (CREB, involved in memory formation) and inactivate glycogen synthase kinase 3 (GSK3), promoting glycogen synthesis and energy storage ( 23 , 33 35 ). Alternatively, IRS can interact with growth factor receptor bound protein-2 (Grb2), ultimately initiating MAPK signaling ( 23 ).…”
Section: Insulin/insulin-like Growth Factor Signaling Pathway Fundame...mentioning
confidence: 99%
“…The synthesis of insect Vg, maturation of oocytes, and uptake of Vg by mature oocytes play pivotal roles in the reproductive development of female insects, which are regulated by crucial hormones [juvenile hormone (JH) and ecdysone (Ecd) ( Roy et al, 2018 ; Santos et al, 2019 )] and multiple signaling pathways. As nutrient sensors, the amino acid/Target of Rapamycin signaling pathway (AA/TOR) and insulin pathway (or insulin-like peptide signaling pathway, ILP) participate in JH and Ecd biosynthesis, interacting synergistically with JH and Ecd to regulate insect yolk formation ( Zhu et al, 2020 ; Dong et al, 2021 ; Pan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%